Eficácia da ozonioterapia aplicada ao tratamento de úlceras venosas - Bomfim, Tássia Lima (2023)
Venous insufficiency is a disease characterized by abnormalities in the functioning of the venous system, caused by valve incompetence, associated or not with obstruction of venous flow, with high prevalence rates. The most advanced stage of the disease is proven with the advent of a venous ulcer, which is a chronic wound that is difficult to heal, with prolonged, high-cost treatment and a negative impact on quality of life. Given this scenario, the central objective of this thesis was to evaluate the effectiveness of ozone therapy as an adjuvant treatment in the healing process. To this end, research was carried out divided into three stages, with different methodological approaches. In the first phase, a systematic review was conducted in order to analyze studies published in national and international databases, which used ozone therapy in the treatment of lower limb ulcers. The search identified 44 studies, of which 7 met the eligibility criteria and totaled 506 patients, aged 18 years and over. The ozone therapy protocols analyzed demonstrated a healing effect in all included studies and none reported adverse effects. Despite this, more studies such as controlled and randomized clinical trials must be carried out in order to prove the effectiveness of this treatment in the healing process. The second phase involved carrying out a methodological study, with the objective of building and validating, through expert consensus, an instrument to evaluate patients with lower limb ulcers, to be applied during the nursing consultation. The innovation of the instrument is highlighted by also incorporating interventions with ozone therapy. The first Delphi round generated changes to the instruments, which were restructured and submitted to a new round, with response rates and agreement of 100% among the judges. The experts considered the instruments valid and capable of guiding nurses in the care of patients with wounds, as well as an efficient tool to guide the recording of nursing care provided. The instruments will be able to qualify nursing practice, by contributing to better patient assessment, directing data collection, identifying nursing diagnoses, introducing ozone therapy in interventions, and thus enriching the record of the nursing process of patients with ulcers in the lower limbs. Finally, a third phase consisted of carrying out a pragmatic clinical trial, with the aim of comparing the healing process of venous ulcers in patients undergoing standard treatment with compression therapy (ABC Model) versus patients who received standard treatment and ozone administration. The results of 22 patients with 6 months of follow-up demonstrated a notable improvement in the healing process and greater reduction in wound area in the group that received ozone therapy. Furthermore, there was a significant positive association between ozone therapy and a lower chance of infection. Therefore, the use of ozone as an adjuvant treatment in patients with venous ulcers appears to be more efficient than standard treatment alone. However, due to the limitations of this study, more research must be carried out in order to confirm our findings.